Preparation method of homogeneous graphite and homogeneous graphite

By coating different types of paste on the surface of the graphite green body layer by layer and controlling the volatile content, the problem of large differences in the density of the inner and outer layers of graphite materials is solved, and the homogeneity of graphite materials is improved and the controllability of performance is achieved.

CN119661225APending Publication Date: 2025-03-21SINOSTEEL NANJING NEW MATERIALS RES INST CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411819405.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Existing graphite materials are affected by various factors during molding, calcining and impregnation, resulting in large differences in the density of the inner and outer layers, affecting the homogeneity and performance of the materials.

Method used

The coating method is used to coat different types of paste on the pre-pressed green body surface, and the volatile content of the blank is gradually reduced from the outside to the inside paste. Through multiple stages of calcination and impregnation, the graphitization is finally carried out to obtain homogeneous graphite.

Benefits of technology

The homogeneity of graphite materials has been improved, and the standard deviations of volume density, flexural strength and resistivity do not exceed 0.004, 0.200 and 0.130, improving the quality controllability and yield of the product.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a preparation method of homogeneous graphite and the homogeneous graphite, and belongs to the technical field of graphite material preparation. The preparation method comprises the following steps: taking raw material fine powder of calcined pitch coke or petroleum coke as aggregate; the raw material fine powder is divided into n parts of fine powder with different weights, the n parts of fine powder are respectively mixed and kneaded with asphalt with different softening points and different amounts to obtain n parts of paste, one part of the paste with the largest weight part of the raw material fine powder is ground into paste fine powder with the average particle size of 10-100 microns, and the other n-1 parts of the paste are subjected to heat preservation; forming the paste fine powder to obtain a pre-pressed green body, sequentially coating (n-1) layers of paste on the surface of the pre-pressed green body, and performing isostatic pressing to obtain a primary green body; and carrying out secondary forming, and carrying out post-treatment to obtain a homogeneous graphite product. According to the method, the surfaces of the pre-pressed blanks are coated with different types of paste materials in a coating mode, so that the green bodies have certain differences from inside to outside, the inside and outside differences caused by follow-up processing to the green bodies are counteracted, and the whole graphite product has the characteristic of uniformity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of graphite material preparation, and in particular relates to a preparation method of homogeneous graphite and the homogeneous graphite. Background Art

[0002] Graphite materials are indispensable key materials in many strategic emerging industries, and their product performance greatly affects the development of downstream industries. At present, the graphite industry has made great progress, and the various properties of graphite have been greatly improved, but it still faces challenges in material homogeneity, which restricts the development of graphite and its downstream industries.

[0003] The inhomogeneity of graphite materials is mainly manifested in the difference between the inside and outside. The density of the graphite blank is affected by many factors. In some aspects, the outer layer has a high density, while in some aspects, the outer layer has a low density. The combination leads to the difference in density between the inner and outer layers, and this difference is uncertain. Generally speaking, the outer layer of the graphite material has a large density and relatively good performance, while the inner layer has a small density and relatively poor performance, and the density of the middle layer will also fluctuate. There are three main reasons for this difference. First, the pressure on the outer surface during molding is greater than that on the inside, so the density of the green body decreases to varying degrees from the outside to the inside; second, the polycondensation reaction of the outer layer of the blank during the roasting process is more intense than that of the inner layer, and more components of the outer layer escape, resulting in a low density of the outer layer of the blank and a high density of the inner layer; third, the penetration depth of the impregnating agent during the impregnation process gradually decreases from the outside to the inside, causing the outer layer of the blank to be impregnated more and the inner layer to be impregnated insufficiently, thereby causing the difference in density between the inside and outside of the blank. The unsatisfactory homogeneity of graphite materials is affected by many factors, and it is difficult to effectively control it with the current production process. And as the size of graphite continues to increase, the difference between inside and outside will become greater, and the industry urgently needs to improve the homogeneity of graphite materials.

[0004] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention and should not be regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art. Summary of the invention

[0005] In order to solve the technical problem in the prior art that graphite materials are affected by various factors, resulting in a large difference in density between inner and outer layers, a preparation method of homogeneous graphite and homogeneous graphite are provided.

[0006] The first aspect of the present invention provides a method for preparing homogeneous graphite, comprising the following steps:

[0007] S1: using fine powder of calcined asphalt coke or petroleum coke as aggregate;

[0008] S2: Divide the raw material fine powder into n portions of different weights, the weight of the n portions of fine powder is not limited, as long as it can be coated. Preferably, the weight of the largest portion does not exceed 50% of the total amount of the raw material, and the weight of the smallest portion is not less than 5% of the total amount of the raw material. More preferably, the weight of the smallest portion is not less than 10% of the total amount of the raw material. The n portions of fine powder are kneaded with asphalts of different softening points and different amounts to obtain n portions of paste. The portion of paste containing the largest portion of raw material fine powder by weight is rolled into a sheet and then ground into a paste fine powder with an average particle size of 10 to 100 μm (the paste is ground after cooling and solidifying), and the other n-1 portions of the paste are kept warm. The role of the heat preservation is to make the paste liquid, which is convenient for subsequent coating. The kneading temperature can be the same or different. Kneading is a basic process. Generally, liquid asphalt is added to the raw material fine powder, and then stirred at a certain temperature (liquid at this time) to obtain a paste. The paste is cooled to become solid, and then ground to obtain a paste fine powder.

[0009] In some embodiments, the weight ratio of n parts of fine powder is not limited, and n parts of raw material fine powder can be any weight ratio that can form a stable core during blank making and facilitate subsequent coating, preferably n:n-1:.....:1;

[0010] In some embodiments, the amount of asphalt used from the inside to the outside of the body is not fixed, and the amount of asphalt used in the outer layer is preferably higher than that in the inner layer, but the asphalt softening point is required to gradually decrease from the inside to the outside, and the volatile matter of the inner layer is ensured to be lower than that of the outer layer, so as to reduce the escape of light components in the inner layer. If too much light components escape from the inner layer, it will be difficult to compensate for it later, resulting in uneven body structure;

[0011] S3: molding the paste fine powder to obtain a pre-pressed green body, and then sequentially coating the n-1 layers of paste on the surface of the pre-pressed green body, and coating the next layer of paste after each layer of paste is coated and cooled, until all coatings are completed, and isostatic pressing is performed to obtain a primary green body;

[0012] S4: Since the core and coating layer of the primary green body have a loose structure, the primary green body is subjected to secondary molding, followed by multi-stage calcination and impregnation, and finally graphitization to obtain a homogeneous graphite product.

[0013] In some embodiments, the fine powder of the paste in step S2 is made of high softening point asphalt, and its volatile content is the lowest among the n pastes. This is because it is relatively difficult to impregnate the inner layer of the green body after calcination, and the volatile content of high softening point asphalt is the lowest at a low dosage, and the paste with low volatile content is relatively stable in the subsequent processing process.

[0014] In some embodiments, the softening point of the asphalt in the paste gradually decreases from the inside to the outside of the primary green body. The asphalt has a low softening point and is easy to volatilize. After baking, pores that gradually decrease from the outside to the inside are formed, which is conducive to subsequent impregnation.

[0015] In some embodiments, the volatile content of the primary green body gradually decreases from the outside to the inside.

[0016] In some embodiments, the average particle size of the pitch coke or petroleum coke is 5 to 50 μm.

[0017] In some embodiments, in step S2, the asphalt softening point is 80-150° C., the asphalt content is 25-40%, and the volatile matter content of the paste can be 10-18%.

[0018] In some embodiments, the molding pressure in step S3 is 10-20 MPa.

[0019] In some embodiments, the molding pressure in step S4 is 150-220 MPa.

[0020] In some embodiments, in step S2, n≥2, preferably, 3≤n≤8.

[0021] A second aspect of the present invention provides a homogeneous graphite prepared by the above-mentioned preparation method, wherein the standard deviation of the volume density of each region in the homogeneous graphite is ≤0.004, the standard deviation of the flexural strength is ≤0.200, and the standard deviation of the resistivity is ≤0.130.

[0022] Compared with the prior art, the gain effect of the present invention is:

[0023] (1) The present invention coats different types of pastes on the surface of the pre-pressed blank layer by layer by coating, so that the green blank has certain differences from the inside to the outside, offsetting the internal and external differences of the blank caused by subsequent processing, so that the final graphite product has uniform characteristics as a whole. The coating method reduces the paste grinding and packaging steps, and can accurately control the coating thickness and uniformity, thereby making the product quality controllable.

[0024] (2) The amount of asphalt and the softening point temperature are important factors affecting the volatile content of the green body paste. The present invention uses asphalts with different softening points and different contents for kneading, and controls the volatile content in the paste to gradually decrease from the outside to the inside of the green body. This not only ensures the stability of the inner layer, but also allows the polycondensation reaction to proceed in stages during the green body roasting process, thereby reducing the damage to the green body caused by the rapid escape of volatiles in the same period of time, and ensuring a high product yield.

[0025] (3) The graphite prepared by the present invention has good uniformity, the standard deviation of the bulk density and the internal and external standard deviation of various properties do not exceed 0.004, the standard deviation of the flexural strength does not exceed 0.200, and the standard deviation of the resistivity does not exceed 0.130. DETAILED DESCRIPTION

[0026] The technical solution of the present invention is described below by specific embodiments. It should be understood that one or more steps mentioned in the present invention do not exclude the existence of other methods and steps before and after the combination step, or other methods and steps can be inserted between these explicitly mentioned steps. It should also be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention. Unless otherwise specified, the numbering of each method step is only for the purpose of identifying each method step, and does not limit the order of arrangement of each method or limit the scope of implementation of the present invention. The change or adjustment of the relative relationship thereof can also be regarded as the scope of implementation of the present invention without substantial changes in the technical content.

[0027] The sources of the raw materials and instruments used in the examples are not particularly limited and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0028] Example 1

[0029] S1: Grind the raw material calcined asphalt coke or petroleum coke into fine powder with an average particle size of 20 μm as aggregate;

[0030] S2: Divide the fine powder into 5 portions of fine powder of different weights, with a weight ratio of 5:4:3:2:1, and knead them with asphalt respectively; knead the largest portion of fine powder with asphalt having a softening point of 150°C to obtain a paste; control the amount of asphalt so that the volatile matter content in the paste is 12.5%; cool and solidify, and then roll and grind into a paste fine powder with an average particle size of 40 μm; knead the other 4 portions of fine powder with asphalt having a softening point of 140°C, 120°C, 100°C, and 90°C in descending order of weight to obtain 4 different pastes; control the asphalt content in the 4 portions of paste so that the volatile matter content in the paste is 13.0%, 13.4%, 13.6%, and 13.8%, respectively; and keep the paste warm after kneading;

[0031] S3: isostatically preform the 40 μm paste fine powder at 10 MPa, and then use 4 different pastes to coat the surface of the pre-pressed green body in descending order of the weight of the fine powder. After each paste coating is completed and cooled, the next paste is coated until all the paste coatings are completed to obtain a primary green body;

[0032] S4: The primary green body is isostatically pressed at 200 MPa, followed by multi-stage roasting and impregnation, and finally graphitization. The roasting temperature is 950°C, the roasting time is 600 h, the graphitization temperature is 3000°C, and the power supply time (graphitization time) is 200 h, so as to obtain a graphite product.

[0033] Example 2

[0034] S1: Grind the raw material calcined asphalt coke or petroleum coke into fine powder with an average particle size of 10 μm as aggregate;

[0035] S2: Divide the fine powder into 6 portions of fine powder of different weights, with a weight ratio of 6:4:3:2:1:1, and knead them with asphalt respectively; knead the largest portion of fine powder with asphalt having a softening point of 150°C to obtain a paste; control the amount of asphalt so that the volatile matter content in the paste is 12.8%; cool and solidify, and grind into a paste fine powder with an average particle size of 20 μm; knead the other 5 portions of fine powder with asphalt having a softening point of 150°C, 140°C, 120°C, 100°C, and 90°C in descending order of weight to obtain 5 different pastes; control the asphalt content in the 5 portions of paste so that the volatile matter content in the paste is 13.3%, 13.7%, 14.0%, 14.2%, and 14.3%, respectively; and keep the paste warm after kneading;

[0036] S3: 20μm paste fine powder is isostatically preformed at 20MPa, and then 5 different pastes are coated on the surface of the pre-pressed green body in descending order of fine powder weight. After each portion of paste is cooled, the next portion of paste is coated until all the pastes are coated to obtain a green body.

[0037] S4: The primary green body is isostatically pressed at 220 MPa, followed by multi-stage calcination and impregnation, and finally graphitization. The calcination temperature is 900°C, the calcination time is 650 h, the graphitization temperature is 2900°C, and the power supply time is 240 h, so as to obtain a graphite product.

[0038] Comparative Example 1

[0039] The same method as in Example 1 is adopted, except that the 5 parts of paste have the same properties, that is, the weight of the raw material fine powder in the 5 parts of the paste is the same, 1 part of the fine powder is kneaded with asphalt with a softening point of 150°C to obtain a paste, and the amount of asphalt is controlled so that the volatile matter content in the paste is 12.5%. After the paste is cooled and solidified, it is rolled and ground into a paste fine powder with an average particle size of 40 μm, and the other 4 parts of fine powder are respectively kneaded with asphalt with a softening point of 150°C, and the amount of asphalt is controlled so that the volatile matter content in the paste is 12.5%.

[0040] Comparative Example 2

[0041] The same method as in Example 1 is adopted, except that the same asphalt is used in different amounts, that is, the fine powder is divided into 5 portions of fine powder of different weights in a weight ratio of 5:4:3:2:1, and they are mixed with asphalt respectively, and the fine powder with the largest weight is mixed with asphalt with a softening point of 150°C to obtain a paste, and the amount of asphalt is controlled so that the volatile matter content in the paste is 12.5%. After cooling and solidification, the paste is rolled and ground into a paste fine powder with an average particle size of 40 μm, and the other 4 portions of fine powder are mixed with asphalt with a softening point of 150°C in order from high to low by weight to obtain 4 different pastes, and the volatile matter content in the paste is controlled to be 12.8%, 13.0%, 13.2% and 13.3%, respectively.

[0042] The differences in various regions of the graphites prepared in Example 1, Example 2, Comparative Example 1 and Comparative Example 2 were compared, and the graphite was sampled in 4 equal parts from the inside to the outside, and its performance was tested and the standard deviation was calculated.

[0043] project Example 1 Example 1 Comparative Example 1 Comparative Example 2 Bulk density standard deviation 0.004 0.004 0.012 0.011 Flexural strength standard deviation 0.194 0.183 0.643 0.557 Resistivity standard deviation 0.122 0.106 0.254 0.218

[0044] As can be seen from the above table, the coating methods of Examples 1 and 2 coat different types of pastes on the surface of the pre-pressed blank layer by layer, and the green blank has certain differences from the inside to the outside, so that the polycondensation reaction is carried out in stages during the green blank roasting process, reducing the damage to the blank caused by the rapid escape of volatiles in the same period, offsetting the internal and external differences of the blank caused by the processing process, so that the final graphite product has uniform characteristics as a whole, and the coating method reduces the paste grinding and packaging steps, and can accurately control the thickness and uniformity of the coating, so that the product quality is controllable, and the standard deviation of the obtained graphite volume density is not more than 0.004, the standard deviation of the flexural strength is not more than 0.200, and the standard deviation of the resistivity is not more than 0.13. The 5 portions of paste in Comparative Example 1 have the same properties, that is, the same raw material subdivision is mixed with the same content and the same softening point asphalt, and a large amount of volatiles escape from both inside and outside during the subsequent roasting process, resulting in larger and more pores, and the pores inside are difficult to be impregnated and supplemented, resulting in a large difference between inside and outside. In Comparative Example 2, the same asphalt is used from the inside to the outside. During the roasting process, as the temperature increases, a large amount of light components escape in the same period of time, which easily leads to uneven green body structure.

[0045] The present invention uses asphalts with different softening points and different contents for kneading, so that the polycondensation reaction is carried out in stages during the green body roasting process, reducing the damage to the green body caused by the rapid escape of volatiles in the same period of time, and ensuring a higher yield rate of the green body.

[0046] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for preparing homogeneous graphite, characterized in that: The steps include: S1: using fine powder of calcined asphalt coke or petroleum coke as aggregate; S2: Divide the raw material fine powder into n portions of different weights, and knead the n portions of fine powder with different softening points and different amounts of asphalt to obtain n portions of paste, and roll the paste containing the largest portion of raw material fine powder into a paste fine powder with an average particle size of 10 to 100 μm, and keep the other n-1 portions of paste warm; S3: molding the paste fine powder to obtain a pre-pressed green body, and then sequentially coating the n-1 portions of paste on the surface of the pre-pressed green body, and coating the next portion of paste after each portion of paste is coated and cooled, and isostatically pressing to obtain a primary green body; S4: secondary molding of the primary green body, followed by multi-stage calcination and impregnation, and finally graphitization to obtain a homogeneous graphite product; Among them, n≥2.

2. The preparation method according to claim 1, characterized in that: The paste fine powder in step S2 uses high softening point asphalt, and its volatile matter content is the lowest among the n parts of the paste.

3. The preparation method according to claim 1, characterized in that: The softening point of the asphalt in the paste of the primary green body gradually decreases from the inside to the outside.

4. The preparation method according to claim 1, characterized in that: The volatile content of the primary green body gradually decreases from the outside to the inside.

5. The preparation method according to claim 1, characterized in that: The average particle size of the asphalt coke or petroleum coke is 5 to 50 μm.

6. The preparation method according to claim 1, characterized in that: In step S2, the asphalt softening point is 80-150° C., the asphalt content is 25-40%, and the volatile matter content of the paste can be 10-18%.

7. The preparation method according to claim 1, characterized in that: The molding pressure in step S3 is 10-20 MPa.

8. The preparation method according to claim 1, characterized in that: The molding pressure in step S4 is 150-220 MPa.

9. The method according to claim 1, characterized in that In the step S2, 3≤n≤8.

10. A homogeneous graphite, characterized in that: The homogeneous graphite is prepared by the preparation method according to any one of claims 1 to 9, wherein the standard deviation of the volume density of each region in the homogeneous graphite is ≤0.004, the standard deviation of the flexural strength is ≤0.200, and the standard deviation of the resistivity is ≤0.130.

Citation Information

Cited By

  • Graphite sagger and preparation method and application thereof

    CN120463499A